PSYCHOEDUCATION THERAPY REDUCES BURDEN AND IMPROVES FAMILY ABILITY IN CARING FOR MENTAL RETARDATION CHILDREN - Sutinah Sutinah; Nofrida Saswati (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Introduction: Children with mental retardation have intellectual functioning below average, inadequate self-care behaviors, socializing, communication, adaptive skills, participation and family support is needed to enhance the independence of the child so that the capability increased and decreased the family burden. Various therapists can be treated to increase the capability of families including family psyche-education therapy. This study is aimed to identify the influence of psycho-education therapy to the family burden and the capability of families in caring for mentally retarded children in SDLB Prof. Dr. Sri Soedewi Masjchun Sofwan, SH Jambi. Method: Quantitative research quasi-experimental, nonequivalent, control group pre-test and post-test design. A sample of 64 respondents consisting of 32 intervention and 32 control with proportional random sampling technique. The data was collected using a structured questionnaire with interview method. Result: The results showed a decrease of the burden and increase the capability of a family in caring for children with mental retardation after psycho-education therapy. Psycho-education therapy is a therapy that can be implemented for a family with psychosocial disorders where exchanged information on mental health care due to the illness suffered, help family members to understand about the disease. Discussion: It is recommended to conduct research that combines psycho-education therapy and supportive therapy to psychosocial support family of children with mental retardation.Keywords: burden, caring capability, mental retardation, psycho-education